Responses of thallus anatomy and chlorophyll fluorescence-based photosynthetic characteristics of two Antarctic species of genus Usnea to low temperature - Hájek, Jan; Hojdová, A; Trnková, K; Váczi, Peter, 1977-; Bednaříková, M; Barták, Miloš, 1963- (Photosynthetica)
Biometrical parameters of two fruticose lichens from Antarctica (Usnea aurantiaco-atra, U. sphacelata) were studied using thallus cross-sections at basal, middle, and apical parts of thallus. The thallus diameter (TD), the thickness of the upper cortex (UCT), distribution of symbiotic alga (Trebouxia sp.) in the algal layer, the thickness of medulla (MT), central cord diameter, and area (CCD, CCA) were measured. U. sphacelata had comparable relative UCT (0.080-0.110, relative to diameter) to U. aurantiaco-atra (0.085-0.130). The relative MT was higher in U. sphacelata (0.240-0.300) than U. aurantiaco-atra (0.080-0.180). In U. aurantiaco-atra, the CCA was two times larger than that in U. sphacelata. Rapid freezing of thalli in liquid nitrogen led to an increase in TD, UCT, CCD because of intrathalline ice crystals formation. Cultivation of symbiotic alga at different temperatures (1.5, 6.0, 15.0, 22.0, and 28.0°C) with repetitive chlorophyll fluorescence parameters measurements showed growth optimum of 15.0°C for potential and effective quantum yield. J. Hájek, A. Hojdová, K. Trnková, P. Váczi, M. Bednaříková, M. Barták. Obsahuje bibliografické odkazy